Evaluasi Praktik Pengalaman Lapangan Mahasiswa Universitas Sunan Giri Surabaya Terhadap Kandungan, Hubungan, dan Manfaat Al Qur’an - Jannah, Rihatul; Ghozali, Sholchan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Field experience practice (PPL) is a program for student practicum activities through learning in peer teaching and actual classroom learning practices. The implementation of this PPL was carried out at Sunan Giri University Surabaya with the aim of increasing understanding regarding the content, relationships and benefits of the Al Quran for human life. The results of the Practical Field Experience Evaluation (PPL) have provided a lot of valuable knowledge and experience for practical students. The theories obtained in lectures can be implemented well in this PPL. Any deficiencies can be covered by the presence of a supervisor so that the self-introspection and evaluation process can run well. This really helps practical students to prepare themselves to enter the real world. Apart from learning, practical students also gain experience in terms of administration and management which students who do not have a PPL program may not necessarily get. So this PPL really helps improve the quality of Islamic Religious Education postgraduate students. PPL runs well, smoothly and according to expectations. Practicing students gain a lot of experience and lecturers also feel helped by having practicums.